Effect of residue management and fertiliser application on the productivity of a Eucalyptus hybrid and Acacia mangium planted on sloping terrain in northern Vietnam. Issue 3 (3rd July 2019) - Van Bich, Nguyen; Mendham, Daniel; Evans, Katherine J; Dong, Tran Lam; Hai, Vo Dai; Van Thanh, Hoang; Mohammed, Caroline L
Abstract : Forest plantation growers in Vietnam commonly burn residues after harvesting and often apply suboptimal amounts of nutrients during plantation establishment. We examined whether the retention of forest residue, and application of phosphorus fertiliser at higher rates, can increase rates of growth. A factorial combination of residue management (burning vs retention) and phosphorus fertiliser application at planting (15 vs 100 kg ha −1 ) treatments were applied at a steeply sloping site in northern Vietnam. Two adjacent experiments were established, one with Acacia mangium and the other with a Eucalyptus hybrid ( Eucalyptus urophylla × Eucalyptus pellita ). Standing volume and leaf area index in A. mangium were greater following burning; this was mostly attributable to the significantly higher survival rate of seedlings. Burning of residues was associated with increases in the number of large branches per tree, and a higher crown damage index (CDI). In the Eucalyptus hybrid, diameter and height responses to the higher rate of fertiliser were observed at age 6 and 12 months, but not beyond. High phosphorus application also led to higher CDI. Standard fertiliser treatment, applied in amounts equivalent to 17, 15 and 8 kg ha −1 of nitrogen, phosphorus and potassium, respectively, was adequate to meet the early growth requirement of eucalypt and acacia plantations at this site. The relatively low amounts of harvest residue and high fertility levels at the site may have masked more significant responses of trees to the silvicultural treatments applied in this study. On steep slopes, especially if soil is poorly fertile, harvest residue retention with adequate weed and termite control may be preferential to burning as it is closely correlated with reducing factors that negatively impact productivity, i.e. water run-off and soil erosion.